Correlation between "hourglass‐like fascicular constriction" and idiopathic anterior interosseous nerve palsy. Issue 4 (23rd December 2016) - Sunagawa, Toru; Nakashima, Yuko; Shinomiya, Rikuo; Kurumadani, Hiroshi; Adachi, Nobuo; Ochi, Mitsuo
ABSTRACT: Introduction : In recent operative cases of anterior interosseous nerve palsy (AINP), hourglass‐like fascicular constrictions have been reported. We prospectively investigated the ultrasonographic history of these lesions to better understand the role of this lesion in AINP. Methods : Seven patients who were diagnosed with idiopathic AINP based on classic clinical findings and had hourglass‐like fascicular constrictions found on ultrasonography were included. All but 1 patient selected surgery, and we followed up all patients clinically and with ultrasonography. Results : In the 5 patients treated surgically in whom paralysis recovered to a level greater than M4, postoperative ultrasonography revealed less constriction. The other patient experienced little recovery after surgery, and the severe constriction remained. In a conservatively treated patient, the paralysis recovered completely, and upon ultrasonography, the constriction had lessened. Conclusions : Although the mechanism is still unknown, hourglass‐like fascicular constriction lessened with relief of motor weakness both in operatively and conservatively treated patients. Muscle Nerve 55 : 508–512, 2017